Valuing cultural ecosystem services - Hirons, M; Comberti, C; Dunford, R (Annual Reviews, 2016)
The ecosystem services (ES) framework was developed to articulate and measure the benefits humans receive from ecosystems. Cultural ecosystem services (CES), usually defined as the intangible and nonmaterial benefits ecosystems provide, have been relatively neglected by researchers and policy-makers compared to provisioning, supporting, and regulating services. Although valuing CES poses several conceptual and methodological difficulties, it is of huge interest and importance because of the linkages between cultural values, valuation methods, and the individual and collective decision-making that influence ecosystems and human wellbeing. This review is not a how-to guide, but rather examines key conceptual issues and maps critical areas of debate. There is a range of potential approaches to assessing CES; however, choices regarding valuation methods and their role in decision-making are shaped by cultural and political dynamics. CES are at a crossroads. They can potentially act as a fruitful conceptual container for a broad range of interdisciplinary research into human-environment relations and transform how decisions regarding the environment are made, but they can also be used to legitimize and entrench modes of decision-making that marginalize and undermine the very values they are intended to protect.